A Translation Analysis Of Noun Phrase In Saman Novel By Ayu Utami - Kurniawati, Denty, Anam Sutopo, S.pd, M.hum, Aryati Prasetyarini S.Pd, M.Pd (2015)
The objectives of this study are (1) to describe the types of translation shift of noun phrase in Samannovel by Ayu Utami and its Indonesian Translation, (2) to describe the equivalence on the Indonesian translation of noun phrase found in the Saman novel by Ayu Utami and its translation. The type of this research is qualitative research. The data source is Saman novel. The data are analyzed by using comparing method. The result of the research show that firstly, there are level shift, structure shift, unit shift, intra system shift. From 378 data, there are 20 or 9% data belong to structure shift, 305 or 80% belong to level shift, 15 or 6% belong to unit shift and 11 or 5% belong to intra system shift. So it means that almost data belong to level shift. Secondly, the equivalence of the data is divided into two, there are: equivalent translation and non equivalent translation. From 378 data, there are 349 or 92% data belong to Equivalent translation, and there are 29 or 8% data belong to non-equivalent. So, it means that the translation of Saman novel by Ayu Utami and Its Indonesian Translation is a good translation because there are almost a half of 349 data belong to equivalent translation.